2015
DOI: 10.1088/0031-9155/60/3/1325
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the repeatability of gamma camera calibration for quantitative imaging applications using a sealed source

Abstract: Several applications in nuclear medicine require absolute activity quantification of single photon emission computed tomography images. Obtaining a repeatable calibration factor that converts voxel values to activity units is essential for these applications. Because source preparation and measurement of the source activity using a radionuclide activity meter are potential sources of variability, this work investigated instrumentation and acquisition factors affecting repeatability using planar acquisition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…The standard deviations within one study and one site were, for each trial, much smaller than the variation of results between the sites. This indicates that modern scintillation cameras provide stable data for repeated studies [34,35]. …”
Section: Discussionmentioning
confidence: 99%
“…The standard deviations within one study and one site were, for each trial, much smaller than the variation of results between the sites. This indicates that modern scintillation cameras provide stable data for repeated studies [34,35]. …”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the technical factors of the SPECT test, including the dose of the radiopharmaceutical, gamma camera calibration and individual factors such as the presence of a bone metabolic disease, renal function, body weight and food intake that may influence the results, [38][39][40] the uptake was measured in a fixed ROI, adding five trans-axial tomographic slides representing the total size of the condyle. This technique reduces intra-operator and inter-operator variability.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al [29] compared the performance of different calibration methods and concluded that a planar acquisition of a point source was sufficiently accurate when scatter and background correction was included in the determination of the calibration factor. Anizan et al [27], [28] investigated the use of sealed 133 Ba sources as 131 I surrogates, with detailed analysis of the factors affecting the repeatability and stability. A general uncertainty analysis of the calibration procedure was also undertaken [34].…”
Section: Conversion From Counts To Activitymentioning
confidence: 99%